African Tourists’ Perceptions of Türkiye’s Image: The Mediating Effects of TV Series and Destination Country Image - KAYA, Muhammet Caner; ALLAMI, Rabiaa; BATMAN, Orhan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study examines the perceptions of African tourists visiting Türkiye by analyzing the structural relationships among country image, TV series, destination country image, and conative intentions. Data were collected from 254 African tourists who had previously visited Türkiye and analyzed using Structural Equation Modeling. Country image showed no significant direct effect on conative intentions; however, its total effect became substantial once the mediators were included. Both television series and destination country image mediated the relationship between country image and conative intentions, with destination country image exerting the stronger influence. All indirect paths were statistically significant. These findings highlight the central role of destination country image in translating national perceptions into behavioral intentions and the complementary, content-driven contribution of TV series. Practically, integrating cultural products with strategies that build destination country image can strengthen destination branding in developing contexts.